Delayed/back up antibiotic prescriptions: what do the public think?. Issue 11 (27th November 2015) - McNulty, Cliodna A M; Lecky, Donna M; Hawking, Meredith K D; Quigley, Anna; Butler, Chris C
Abstract : Objective: To describe the general public's understanding, acceptance and use of delayed antibiotics. Design: Face to face computer-assisted survey using an Ipsos MORI Capibus survey. Setting: Randomly selected households in England using multistage sampling. Respondents: A representative sample of 1625 adults aged over 15 years and recruited from household visits in England, using age and gender quotas for each area. Data collection and analysis: The survey was undertaken in January 2014. Weights based on gender, age, ethnicity, working status, social grade, housing tenure and Government Office Region corrected for selection biases, so that results are broadly representative of the population. Main outcomes measures: Proportion of respondents; understanding the meaning of the term delayed antibiotic prescription and how the strategy is used in general practice; in favour of, or opposed to clinicians offering them a delayed antibiotic; reporting receipt, use and acceptability of delayed antibiotic prescriptions in the past year. Results: 17% reported fully understanding the meaning of delayed antibiotic prescription and strategy use in general practice;72% were unaware of the term or strategy; 36–39% were in favour of, and 28–30% opposed to clinicians offering them a delayed antibiotic for throat, urine, ear or chest infections. Half of those who were fully aware of the term and practice were in favour of delayed antibiotics. Women, and older respondents, were more strongly opposed to delayed prescribing. Only 4% of all respondents, and 15% of those prescribed an antibiotic, reported being offered a delayed antibiotic in the last year. Conclusions: Wider understanding and acceptance of delayed prescribing may facilitate increased uptake. Further research is needed to determine why groups are so strongly in favour or opposed to delayed prescribing.